Emerging Technologies in Agriculture and Medicine Innovations for Global Health and Food Security - Bibi, Tahira; Mengal, Samina; Irfan, Shazia; Behlil, Farida; Jamil, Nelofer; Khan, Nazima Yousaf; Tareen, Niaz Muhammad; Masood, Ayeesha; Ahmed, Hina Ali; Sajjad, Naheed (Journal of Neonatal Surgery, 2025)
Global health and food security are increasingly threatened by population growth, climate change, and emerging diseases. To address these challenges, the integration of advanced technologies in agriculture and medicine offers innovative pathways for sustainable development and resilient societies. This study investigates how emerging technologies in agriculture and medicine can provide integrated solutions to address global health challenges and food security, with a focus on innovations that enhance sustainability, efficiency, and resilience. A cross-disciplinary analysis was conducted using peer-reviewed articles, global case studies, and recent technological reports published between 2015 and 2025. Data were synthesized to evaluate applications of CRISPR-based gene editing, precision agriculture, nanotechnology, artificial intelligence, regenerative medicine, and digital health tools, with particular attention to their synergistic roles in advancing health and food systems. The results of this study demonstrates that gene-edited crops, smart irrigation, and drone-enabled monitoring significantly improve yield, climate resilience and resource optimization. In medicine, Nanotechnology, AI-driven diagnostics, and personalized therapeutics express measurable improvements in disease prevention and treatment efficiency. Importantly, cross-sectoral innovations such as biofortified crops reducing malnutrition, agricultural platforms supporting vaccine production, and nutraceuticals linking agriculture to preventive health illustrate the interconnected benefits of these technologies. Emerging technologies are reshaping agriculture and medicine, offering transformative strategies for sustainable food production and improved health outcomes. However, global implementation requires addressing challenges of accessibility, ethical governance, and policy integration, particularly in low- and middle-income regions. Harnessing these innovations within robust regulatory and equitable frameworks can strengthen resilience against future health and food security crises